Wedding planner's deal with the CEO - Milne, Nina (Harlequin Enterprises ULC, 2023)
"Poppy Winchester's wedding-planning company desperately needs rescuing. The only person she knows who can help is her former best friend, self-made billionaire Nathan Larrimore. So Poppy makes a deal with him that benefits them both. But seeing widower Nathan again brings suppressed, and inconvenient, desire to the surface! Forced together on a whirlwind business trip to Copenhagen, they're given a chance to overcome their past and perhaps make a fresh start neither saw coming!"--back cover.